MODELING SHOES IN UNIVERSAL 3D GRAPHICS PROGRAMS - Каменець, С. Є.; Захожа, Н. Ю. (Fashion Industry, 2022)
The article describes the development of methods of 3D modeling and design of fashion industry products using universal computer programs 3D graphics. Purpose: To increase the competitiveness of shoe production and the quality of design training through computerization and introducing the latest information technologies in the design and manufacture of fashion industry products, namely the use of universal 3D modeling systems for shoe design. Research results. There are many computer-aided shoe design systems in the world that are successfully used by large shoe companies. However, they are very expensive, and many medium and small businesses cannot use them. This 3D method of modeling shoes was made just for small businesses. This affordable graphics program, Rhinoceros, uses a spline method of representing spatial objects. To test the proposed methodology, the shoe trends of 2021 were analyzed and a model of women’s boots was made. Scientific novelty. It was created with the method of three-dimensional modeling of shoes. NURBS technology (Non-Uniform Rational B-Spline) allows companies to calculate the geometric position of each point on the surface of the future shoe model with high accuracy. After this it is possible to create templates or to make a prototype using 3D printers or CNC devices. Practical significance. A method is proposed for obtaining a 3D model of shoes, accessories and accessories of the fashion industry in a universal 3D graphics editor. It is available for small and mediumsized businesses, which allows the authors of the object being created to see, evaluate and correct, if necessary, a future product even before creating its prototype. Spatial models provide an opportunity to present a product to customers, estimate future costs and improve the quality of design preparation for production. In addition, it is possible to obtain 2D details of the future product.